Food in Anglo-Saxon literature: food dichotomies - Lendinara, Patrizia (E|C, 2020)
The numerous works in Anglo-Saxon prose, even if not expressly dedicated to food, allow us to analyze the contemporary attitude towards it. The selected case studies offer significant data on the society of the time and its articulation: among the examples in question, whose examination is based on the analysis of the corpus in Anglo-Saxon vernacular, the duality of raw and cooked could not be missing, with regard to oyster, a mollusk then common in England, and meat. Within the dichotomy between laymen and monks, another contrast is played out that will be investigated, that between the quadrupeds, whose meat was banned from the monastic diet, and the other animals. The lexicon expresses the distinctions of the Rules, but reveals the difficulty of the choices, not only linguistic. The analysis of some diet-related behaviors, as represented in the analyzed texts, allows us to grasp the internal tensions in social actions.